EXPLORING THE IMPACT OF AI WRITING TOOLS ON UNIVERSITY STUDENTS’ SYNTHESIS SKILLS IN ACADEMIC WRITING - Gadis Pujawiyanti; Fahrus Zaman Fadhly (Universitas Kuningan, 2025)
The data were thematically analyzed to explore patterns in students’ writing behaviors and perceptions. Findings indicate that while AI tools assist in organizing ideas and paraphrasing content, they may also reduce critical engagement with source materials.To investigate trends in the writing habits and attitudes of the students, the data underwent a thematic analysis. Results show that whereas AI tools help with content paraphrasing and concept organization, they may also lessen critical interaction with source materials. The depth of synthesis is weakened when students rely on AI to combine information without fully processing it. Others, on the other hand, begin with AI and then separately integrate sources. In order to foster real synthesis and academic integrity, the study emphasizes the necessity of instructional assistance in encouraging the thoughtful and ethical use of AI tools.